Budaya Tabayyun dan Toleransi Berpendapat Tinjauan Literatur Etika Berdiskusi di Era Informasi - Aziz, Nadya Chairunnisa (Maliki Interdisciplinary Journal, 2026)
The digital era brings challenges like hoaxes and polarization threatening opinion tolerance. This descriptive-analytic literature review examines tabayyun culture (information verification based on QS Al-Hujurat:6) as the foundation of Islamic discussion ethics. Descriptively, tabayyun fosters critical behavior to prevent slander; analytically, it complements tolerance through active listening, musyawarah dialogue, and 7 Quranic ethics. In multicultural Indonesia, it addresses digital radicalism and echo chambers. Key findings: Integrating tabayyun realizes wise communication, reducing hate speech. Recommendations include national literacy programs by Kemenag-Kominfo, educational curricula, community forums, and empirical research. This study contributes the "Tabayyun Tolerant" model for contemporary digital literacy. Therefore, strengthening digital literacy based on the values ​​of tabayyun through education, government policies, and community participation is a crucial step in addressing communication challenges in Indonesia's multicultural society. Thus, the "Tolerant Tabayyun" model can be an alternative solution in building a peaceful and responsible digital communication culture.